2014
DOI: 10.1007/s00606-014-1175-9
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis of Jarava (Poaceae, Pooideae, Stipeae) and related genera: testing the value of the awn indumentum in the circumscription of Jarava

Abstract: Jarava, a genus of the tribe Stipeae with 31 American species, is considered polyphyletic. In previous phylogenetic analyses, despite a few species of Jarava were used, they were included in the Major American Clade (MAC) together with species of Achnatherum, Amelichloa and Nassella. The main goal of this study is to test the monophyly of Jarava and to estimate relationships of Jarava species and allied genera. Eighty-nine species of Stipeae (17 species of Jarava) were included in the analyses of trnH-psbA and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 26 publications
(52 reference statements)
1
5
0
Order By: Relevance
“…Elias) Barkworth, 5 spp., North America); Jarava Ruiz & Pav. (30 spp., Central & South America; Sclovich et al, 2015); Lorenzochloa Reeder & C. Reeder (8 spp., South America, including Anatherostipa s.s., leaving four spp. unplaced; Romaschenko, 2021, pers.…”
Section: Discussionmentioning
confidence: 99%
“…Elias) Barkworth, 5 spp., North America); Jarava Ruiz & Pav. (30 spp., Central & South America; Sclovich et al, 2015); Lorenzochloa Reeder & C. Reeder (8 spp., South America, including Anatherostipa s.s., leaving four spp. unplaced; Romaschenko, 2021, pers.…”
Section: Discussionmentioning
confidence: 99%
“…The ITS sequences were also shown to be useful for assessing evolutionary relationships among closely related grass species for example within the genera of Bromus 22 , Miscanthus 23 , Hordeum 24 , Elymus 25 , Setaria 26 and Festuca-Lolium complex 27 . However, the literature data have shown that phylogenetic trees derived from ITS sequences were unresolved within clades comprising Stipa 3 , 28 . The branch of ITS-based cladogram published by Hamasha et al .…”
Section: Discussionmentioning
confidence: 99%
“…a few nuclear markers and several plastid markers were applied. Among nuclear loci usefulness of internal transcribed spacers (ITS) was tested both as a complete ITS 15 , 17 , 20 and separately as ITS1 and ITS2 19 , 21 . Moreover, external transcribed spacer (ETS) was applied in one study 19 .…”
Section: Introductionmentioning
confidence: 99%